The difficulties in the academic process capable of producing resilience, according to Spanish university students of nursing - Álvaro Bernalte Benazet; María Teresa Miret García; Cristina María Navarro Carrasco; Soledad Ruiz Martel; María Teresa Bermúdez Ferreiro; María Mercedes Lupiani Jiménez (Universidad de Alicante, 2012)
The resilience is not a new concept, in fact the authors dedicated to his study, they admit the proliferation of articles about the topic and assume that it exists at par of the humanity. In the present study, we understand the resilience as the aptitude of the human beings to overcome adversities and to learn of it to continue with the daily life, the interest of the same one is that we have studied the adversities or difficulties that the pupils recognize like capable of producing resilience, instead of making it from the point of view discipline, of the professional, they will be analyzed from the point of view of the actors, in this case the student body of a University School of Nursing of Algeciras (Spain). The present work is a qualitative research, from the point of view cultural sight (least used in the study of the resilience), and we have used two associate technologies, namely: a Technology Delphi and one of nominal Group, later to confirm the obtained results, with the contributions with Brainstorming's Technology. Between the results, it surprises that one that the pupils consider to be adversities or difficulties, and particularly the fact that the academic aspects that scarcely were supported as difficulties on having ended the Technology Delphi, they appear in the last technology, of contribution of ideas and therefore more creative, of forceful form.